Nutritional factors in the pathogenesis of ear disease in children: a systematic review. (29th September 2015) - Elemraid, M; Mackenzie, I; Fraser, W; Brabin, B
Abstract : Background: Ear disease is a major health problem in poorly resourced countries. The role of nutritional deficiencies in its pathogenesis and in relation to chronic suppurative otitis media (CSOM) has not been reviewed previously. Aim: To evaluate the evidence linking specific nutrient deficiency with middle-ear disease and infection, particularly CSOM, and the potential influence of multi-micronutrient deficiency. Methods: A systematic review was undertaken using Medline on Pubmed, SCOPUS, Cinahl on Ovid, the Cochrane Database of systematic reviews and selected medical journals, with no language restriction. Nutritional mechanisms potentially related to ear disease and CSOM risks were reviewed. All studies (observational, case-control, cohort and clinical trials including randomised controlled trials) with nutrition-related information were included. The titles and/or abstracts of all retrieved studies were reviewed and full articles were obtained for relevant studies. Exclusion criteria were multiple publication or studies which did not report nutritional information. Results: Supplementation studies using single micronutrients and vitamins to determine efficacy in reducing acute or chronic otitis media provided some evidence for an association of middle-ear pathology with deficiencies of zinc or vitamin A. Multi-micronutrient supplementation studies provided further support for a beneficial effect, although the number of studies was small and they were heterogeneous and uncontrolled. No human study was identified which specifically examined the association between copper, selenium or vitamin D status and middle-ear disease or infection. Conclusion: Particularly in developing countries, research on micronutrient status and vitamin deficiency and their influence on middle-ear disease is required to improve knowledge of the pathogenesis of middle-ear infection and to determine the relevance of nutritional interventions in prevention and treatment.